Threat Calls, Terrorism Challenges and Security Issues Towards Malaysia - Md Ramlan, Saiful Farisin; Ahmad, Mohd Rusydi; Chin, Yew Wong; Sabtu, Muhamad Helmy (Journal of Techno-Social, 2022)
Abstract: National security receives threats from various angles through the process of globalization. Threat calls, terrorism and security issues pose a risk to the country as they affect the stability of the government and threaten the safety of the people. The rapid globalization process has led to the weakening of the nation and eroded by various demands and threats. Malaysia is also no exception to the challenge of the speedy globalization process. The issue of security is not merely an issue that concerns the defense agenda of a country, but rather covers various aspects, especially those related to human society. Malaysia's experience in dealing with terrorism in the past has led governments to be cautious of any possible consequences. In fact, the threat of terrorism and issues related to security issues in Malaysia need to be clearly understood in order to look at the trends and long-term effects on society, the economy, politics and social as a whole. The activities and behaviors of terrorism and security threats are also unpredictable apart from its difficult to understand movement. Political stability, economic development and the well-being of the people are essential to maintaining peace and ensuring national security. This paper reviews the threats and challenges of terrorism and security issues specifically towards Malaysia.